Connecting structural changes to cell transformation patterns in the canine degenerative mitral valve - Abbott, Kaitlin Marie, author; Orton, E. Christopher, advisor; Frye, Melinda, committee member; Schenkel, Alan, committee member (Colorado State University. Libraries, 2015)
Degenerative mitral valve disease (DMVD) is a significant problem in the canine population and also affects humans. Recent studies have provided insight into molecular and cellular mechanisms that likely contribute to disease progression. Better understanding of the cellular processes that mediate the degenerative process could lead to treatments that prevent or slow this degeneration benefiting both canine and human patients. Structural changes to degenerative valves such as nodules, leaflet thickening, increased opacity, loss of elasticity and loss of valve architecture have been well documented. Abnormal cell transformation patterns such as the transformation of valvular interstitial cells to activated myofibroblasts have been characterized in degenerative mitral valve tissue, as well as other irregular cell behavior such as the overproduction of glycosaminoglycan and matrix remodeling factors that have become hallmarks of the disease. Despite these important discoveries, much remains unknown about cell signaling in degenerative mitral valve disease and how cell activity changes a normal valve to the diseased phenotype. An overarching hypothesis of this study is that investigating signaling mechanisms active in degenerative valves could provide insight into cellular processes mediating the disease. A specific hypothesis that emerged from initial results is that endothelial to mesenchymal transition (EndMT), a process important in valvulogenesis, could be active in degenerative mitral valves. The first goal of this study was to compare protein abundance in degenerative and normal mitral valves to determine if there exists previously unidentified signaling molecules that could be initiating or perpetuating the cellular transformations and abnormalities present in DMVD. The second goal was to investigate these proteins using immunohistochemistry to characterize their activity in the tissue matrix and show evidence of their contribution to structural changes of the valve. The first goal was accomplished by doing a targeted microarray analysis of signaling proteins comparing their relative abundance in normal and degenerative mitral valves. This analysis yielded an increased abundance of signaling proteins that have been associated with EndMT. The second goal was accomplished by immunohistochemistry to determine the spatial distribution of selected proteins from the microarray analysis with markers of endothelial cells and mesenchymal cells (activated myofibroblasts). Targeted microarray analysis of signaling proteins revealed increased abundance of 18 proteins including the growth factor HB-EGF, its partner molecule ADAM17, and the cell adhesion molecule integrin β3, all possible mediators of EndMT (Chapter 4). Immunohistochemistry studies demonstrated the presence of cells positive for the endothelial marker CD31 within the valve interstitum. These CD31 positive cells co-localized with areas of myofibroblast transformation in degenerative valves identified by positive staining for α-smooth muscle actin (αSMA). Expression of signaling proteins including HB-EGF and ADAM17 also co-localized to these areas (Chapter 5). In conclusion, these results support active EndMT in canine degenerative mitral valves. EndMT could be contributing to the formation of high cellular density myofibroblast transformation which has been postulated to mediate mitral valve degeneration.
Keywords: degenerative mitral valve